Hybrid periodic carrier frequency modulation technique based on modified SVPWM to reduce the PWM noise. Issue 3 (14th January 2019) - Huang, Yingliang; Xu, Yongxiang; Zhang, Wentao; Zou, Jibin
Abstract : This study proposed a hybrid periodic carrier frequency modulation (HPCFM) technique based on the modified space vector pulse‐width modulation (SVPWM) for two‐level three‐phase voltage source inverters to eliminate the PWM noise. Owing to PWM technique and switching losses considerations, ear‐piercing high‐frequency acoustic noise from motor is common. The proposed HPCFM technique is able to remove the high‐frequency unpleasant acoustic noise more effectively than conventional PCFM with lower switching losses and shorter frequency range. In addition, the PWM harmonics in phase voltage and phase current are reduced significantly. Furthermore, the HPCFM method is simple to implement and does not employ additional circuits in drive system. The effectiveness of the proposed approach has been confirmed by detailed experimental results.